Prospective scenarios for the personal responsibility promotion with health in Cuba until 2030 - Isabel Pilar Luis Gonzalvez; Yusdanys Torres Jimenez; Adolfo Gerardo Álvarez Pérez (Medisur)
Foundation: scenario construction methods are of great importance for the achievement of any goal since they allow social actors to participate in the construction of the desired future by conjecturing the realities that have not yet happened but that could happen if the action is anticipated. Objective: to develop prospective, exploratory scenarios to promote higher levels of personal responsibility with health in Cuba until 2030. Methods: strategic prospective study from January 2018 to March 2020 with the application of the Cross Impact Systems and Matrices method and the LIPSOR-EPITA-SMIC-Prob-Expert ® software. 16 experts were selected who evaluated the simple and conditional probabilities of occurrence of six hypotheses that represented possible futures. Results: a total of 64 scenarios were obtained, of which ten were considered trend scenarios. The chosen scenario was “Accept the changes, manage the challenges, integrate the process”, which form a narrative with the fulfillment of five of the six hypotheses evaluated. Conclusions: the application of the Cross Impact Systems and Matrices method allowed elaborate possible future scenarios that must be challenged to promote higher levels of personal responsibility with health in Cuba on a horizon until the year 2030. It is proposed to complete the exercise of strategic foresight, assessing the policy principles, strategies and actions to be included in a policy or strategic action plan to achieve the target scenario.